Pengembangan Media Monopoli Petualangan Nusantara (MONPERA) Pada Pembelajaran IPS Kelas IV SD Negeri 2 Banjarsari - Putri Rifani; Muhammad Fatwa Khusni; Tias Kumala Dwi (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
This study aims to (1) develop MONPERA media in social studies learning for Elementary School grade IV students, (2) determine the appropriateness of MONPERA media, (3) determine students’ responses and teacher’s responses to MONPERA media in Social studies subject class IV Elementary School, (4) know the increasein social studies learning achievement of fourth grade students of Banjar Sari 2 Elementary School after using MONPERA media.This type of research is research and development (RD).The research subjects 15 grade IV students. Development procedures are research and data collection, planning, product draft development (develop preliminary for mof product), preliminary field testing, revising test results (main product revision), testing field testing (main field testing), and product refinement of field test results (operational product revision).